问题 解答题
先化简,再求值:
(1)(a-
2ab-b2
a
)•
a2+ab
a2-b2
,其中a=1,-3<b<
3
且b为整数;
(2)
m-3
3m2-6m
÷(m+2-
5
m-2
)
,其中m是方程x2+3x-1=0的根.
(3)化简分式(
x
x-1
-
x
x2-1
x2-x
x2-2x+1
,并从-1≤x≤3中选一个你认为合适的整数x代入求值.
答案

(1)原式=

a2-2ab+b2
a
a(a+b)
(a-b)(a+b)

=

(a-b)2
a
a(a+b)
(a-b)(a+b)

=a-b;

∵a2-b2≠0,

∴当a=1时,b≠±1.

①a=1,b=-2时,原式=1+2=3;

②a=1,b=0时,原式=1-0=1;

(2)原式=

m-3
3m(m-2)
÷(
m2-4
m-2
-
5
m-2

=

m-3
3m(m-2)
÷
(m-3)(m+3)
m-2

=

m-3
3m(m-2)
m-2
(m-3)(m+3)

=

1
3(m2+3m)

=

1
3

(3)原式=

x2+x-x
(x-1)(x+1)
(x-1)2
x(x-1)

=

x
x+1

当x=2时,原式=

2
2+1
=
2
3

判断题
单项选择题